The Content of the Pedagogical Process to Develop the Knowledge of Future Physical Education Teachers About Sports Tourism - Muzaffa, Boltayeva Sumbula (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article describes the peculiarities of training future physical education teachers for sports tourism, opinions on the development of various reforms in society.